THE BENEFITS OF ROLE-PLAYING GAMES IN DEVELOPING SPEAKING PROFICIENCY AMONG YOUNG LEARNERS - Egamberganova Gulnoza Ulug'bek qizi (PEDAGOGS, 2024)
Abstract: This article explores the benefits of role-playing games (RPGs) as an innovative educational tool for developing speaking proficiency among young learners in grades 5 to 9. It highlights how RPGs create immersive environments that reduce anxiety and encourage communication, allowing students to practice language skills in a low-pressure setting. The article discusses the social interaction fostered by RPGs, which enhances vocabulary acquisition and fluency through collaborative storytelling and problem-solving. Additionally, it examines the role of technology in facilitating these experiences, including the use of digital platforms, virtual reality (VR), and analytics tools that support personalized feedback and progress tracking. The findings suggest that integrating RPGs into language education not only improves speaking skills but also promotes critical thinking and teamwork among students, making it a valuable approach in modern classrooms.